A mini-review on functional magnetic resonance imaging on brain structure of vascular cognitive impairment - Wei, Zeyi; Yue, Jinhuan; Li, Xiaoling; Zhao, Weiwei; Cao, Danna; Li, Ang; Yang, Guanhu; Zhang, Qinhong (Frontiers in Neurology, 2023)
Vascular cognitive impairment (VCI) is the initial stage of vascular dementia (VaD). Early diagnosis and treatment of VCI are crucial to prevent the progression of VaD. In order to gain a better understanding of VCI, this study aimed to investigate the use of advanced imaging techniques such as structural magnetic resonance imaging (sMRI) and resting-state functional magnetic resonance imaging (rs-fMRI). These techniques allow researchers to observe the structural and functional changes in the brain that are associated with VCI. Functional magnetic resonance imaging (fMRI) and sMRI techniques have been widely used in studies focusing on gray matter, brain networks, and functional abnormalities during rest. By searching and summarizing recent literature, this study has provided valuable evidence on the use of advanced imaging techniques in understanding and treating VCI. The findings from this study can aid in the development of early intervention strategies for VCI patients, potentially slowing down or even halting the progression of VCI to full-blown VaD.